Hydrogen production from water-splitting reaction based on RE-doped ceria-zirconia solid-solutions - Dasari, Hari Prasad; Ahn, Kiyong; Park, Sun-Young; Ji, Ho-Il; Yoon, Kyung Joong; Kim, Byung-Kook; Je, Hae-June; Lee, Hae-Weon; Lee, Jong-Ho (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
The effect of rare earth (RE = Tb, Pr and La) dopant on the catalytic performance of RE-doped ceria-zirconia (CZRE) solid-solutions for oxygen storage capacity and hydrogen production activity has been successfully investigated. The sustainability of the solid-solutions even after the reduction was confirmed by XRD. Raman analysis showed that the addition of RE element in CZ system significantly decreased the intensity of the characteristic fluorite peak (462-474 cm(-1)) indicating a highly deformed structure than CZ system which can enhance the oxygen mobility and redox property of these materials and the order of the intensity decrease was Pr > Tb > La. The XPS measurements revealed that the CZPr sample has a homogeneous distribution of Ce/Zr and also showed a high enrichment of Pr on the particle surface than the others. Among the CZRE solid-solution catalysts tested, CZPr catalyst showed the best catalytic performance for high OSC and hydrogen production from water-splitting reaction. Copyright (C) 2013, Hydrogen Energy Publications, LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: GLYCINE-NITRATE PROCESS; MIXED OXIDES; STRUCTURAL-CHARACTERIZATION; CATALYTIC PERFORMANCE; REDOX BEHAVIOR; X-RAY; ELECTROLYSIS; CELLS; POWDERS; CEXZR1-XO2